2017
DOI: 10.1038/s41598-017-08559-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of androgen excess on maternal metabolism, placental function and fetal growth in obese dams

Abstract: Pregnant women with polycystic ovary syndrome (PCOS) are often overweight or obese. To study the effects of maternal androgen excess in obese dams on metabolism, placental function and fetal growth, female C57Bl6J mice were fed a control (CD) or a high fat/high sucrose (HF/HS) diet for 4–10 weeks, and then mated. On gestational day (GD) 15.5–17.5, dams were injected with dihydrotestosterone (CD-DHT, HF/HS-DHT) or a vehicle (CD-Veh, HF/HS-Veh). HF/HS dams had higher fat content, both before mating and on GD18.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…It has been reported that maternal androgen excess in rats, alters placental steroidogenesis and leads to dysregulation of lipid metabolism in their adult female offspring (Sun et al, 2012). Likewise, prenatal androgen excess affects fetal liver function with increased triglyceride content and alters expression of enzymes and transcription factors involved in de novo lipogenesis and fat storage (Fornes et al, 2017). In this context, we have previously demonstrated that prenatal hyperandrogenism induces liver alterations and impairs the balances of both lipid metabolism and systemic insulin and glucose metabolism (Abruzzese et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…It has been reported that maternal androgen excess in rats, alters placental steroidogenesis and leads to dysregulation of lipid metabolism in their adult female offspring (Sun et al, 2012). Likewise, prenatal androgen excess affects fetal liver function with increased triglyceride content and alters expression of enzymes and transcription factors involved in de novo lipogenesis and fat storage (Fornes et al, 2017). In this context, we have previously demonstrated that prenatal hyperandrogenism induces liver alterations and impairs the balances of both lipid metabolism and systemic insulin and glucose metabolism (Abruzzese et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…To ensure that the HFD induces maternal obesity, some studies mate HFD females when their body weight has increased by a certain amount, and compare these with age-matched females on a control diet. In mice, this approach increased fetal weight in two studies [97, 98], had no effect in another [132], and decreased fetal weight in a fourth [90]. Ye et al [115] fed rats a HFD and selected those with the greatest weight gain (susceptible to diet-induced obesity) and those with the lowest weight gain (resistant to diet-induced obesity) and found that fetal weight was reduced in susceptible dams but not in resistant dams.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental approaches that increase fetal growth are suitable for modeling high birthweights, which occurs at higher frequency in obese pregnancies [6, 10]. Mating HFD mice when their weight had increased by 25% led to higher fetal weight in two studies [97, 98] but had no effect in another [132]. While the solid component of the HFD was 41% fat in these studies, the provision of a sucrose solution with the HFD would have reduced the percentage of calories from fat (and protein), perhaps to levels more typical of Western diets.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that during pregnancy, the fetus is particularly exposed to various signals from the mother. Furthermore, particular genes’ expression changes can be associated with an increased risk of metabolic and reproductive disorders in postnatal life [19]. Increased glucocorticoid and/or androgen exposure during critical periods of embryonic development can cause the developmental programming of PCOS in humans and animals [14,20].…”
Section: Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%